Development of a lab based epee fencing protocol - Bottoms, L.; Sinclair, J.; Rome, P.; Gregory, K.; Price, M. (International Journal of Performance Analysis in Sport, 2013)
The aims were to undertake a movement analysis of a simulated epee fencing competition and to develop and validate a laboratory based protocol (LAB). Seven male club epee fencers undertook a simulated competition (SIM) comprising of the 'Poule' and 'direct elimination' (DE) structure of competition. Video analysis was completed to identify fencing specific movements and work to rest ratios from which a LAB was developed. Six different fencers undertook the second part of the experiment involving the LAB. Heart rate and RPE were monitored throughout both trials. Statistical analysis was undertaken to compare HR and RPE responses within and between SIM and LAB. A work to rest ratio of 9:8s was calculated for the Poule and 10:12s for the DE. Poule (first round) fights lasted 139 ±12 s whereas a DE fights lasted 491 ±20 s. Although HR was lower during the DE phase of LAB, a similar intensity to those reported for previous fencing competitions was elicited. Lower HR during the second phase of the LAB is likely due to lower circulating adrenaline in a non competitive situation. However, based on mean HR and RPE responses and specific movement patterns involved the protocol may be useful for examining interventions.